Principles And Problems Underlying Testing The Effectiveness Of Blast Protective Footwear - Chaloner, E J; McMaster, J; Hinsley, D E (BMJ military health, 2002)
Anti-personnel landmines are a continuing threat to soldiers and civilians working overseas in post conflict situations. Several groups of governmental and commercial scientists are currently designing and/or testing footwear to protect the lower leg from the effects of close proximity blast. The general principles surrounding testing of protective footwear are examined together with an assessment of the known progress to date and the strengths and weaknesses of the designs produced.